2018
DOI: 10.1007/s12639-018-1000-4
|View full text |Cite
|
Sign up to set email alerts
|

Is the cattle tick Rhipicephalus annulatus Say, 1821 reared on the rabbit?

Abstract: The cattle tick Say, 1821 (Acari: Ixodidae) is the main tick species on cattle in Egypt. This study was designed to know the possibility of rearing on rabbits in order to obtaining an adequate tick number and maintaining this tick species in lab to the next generation. Additionally, a comparison was performed between some biological parameters in fed on rabbits with that fed on cows. Six New Zealand white rabbits were used as a lab animal for rearing. The animals were divided into two groups. The first (G1) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…Infected adult ticks fed on rabbits took a slightly longer time (+26.8 days) than non-infected ticks to complete their life cycle. This finding agrees with that reported by some researchers [ 44 , 45 ], who reared R. decoloratus and R. annulatus ticks on non-infected rabbits. They found that R. annulatus and R. decoloratus larvae and nymphs molt on rabbits, whereas females fed slowly for 5 days without being partially engorged.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Infected adult ticks fed on rabbits took a slightly longer time (+26.8 days) than non-infected ticks to complete their life cycle. This finding agrees with that reported by some researchers [ 44 , 45 ], who reared R. decoloratus and R. annulatus ticks on non-infected rabbits. They found that R. annulatus and R. decoloratus larvae and nymphs molt on rabbits, whereas females fed slowly for 5 days without being partially engorged.…”
Section: Discussionsupporting
confidence: 93%
“…They found that R. annulatus and R. decoloratus larvae and nymphs molt on rabbits, whereas females fed slowly for 5 days without being partially engorged. We calculated the life cycle of R. annulatus on clean rabbits as 71–84 days with a mean of 76.9 days, whereas Abdel-Shafy (2018) calculated the life cycle as 59–82 days with a mean value of 70 days [ 44 ]. Six New Zealand white rabbits were used for rearing R. annulatus .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, the remaining tick genomes encoded between 39 and 97 EVEs. This disparity between tick genomes in EVE numbers and diversity is of particular interest; the two species with the fewest Mononegavirales-derived EVEs (Rhipicephalus annulatus and Rhipicephalus microplus, each with only a single rhabdoviral EVE identified) retained abundant parvoviral EVEs yet are both single-host ticks (all three life stages feed and develop on the same host [39,40]) and thus may have fewer opportunities to acquire viruses from multiple diverse vertebrates than do the other ticks featured in our analysis which utilize three hosts during their life cycle [21,[41][42][43][44][45][46]. The tree is manually rooted on Polydnaviridae.…”
Section: Resultsmentioning
confidence: 99%